2009
DOI: 10.1158/1078-0432.ccr-08-2132
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative Breast Cancer: Distinguishing between Basal and Nonbasal Subtypes

Abstract: Purpose: Triple-negative (TN; estrogen receptor, progesterone receptor, and HER-2 negative) cancer and basal-like breast cancer (BLBC) are associated with poor outcome and lack the benefit of targeted therapy. It is widely perceived that BLBC and TN tumors are synonymous and BLBC can be defined using a TN definition without the need for the expression of basal markers. Experimental Design: We have used two well-defined cohorts of breast cancers with a large panel of biomarkers, BRCA1 mutation status, and follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
367
4
16

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 432 publications
(403 citation statements)
references
References 51 publications
16
367
4
16
Order By: Relevance
“…This subgroup present a greater genetic complexity compared with other BC subtypes, suggesting a greater degree of genetic instability [28,29]. Bergamaschi [30] found that BLBC show the highest frequency of DNA losses and gains compared with others subtypes and also reported that despite of the highest prevalence of genomic aberrations, BLBC show less genomic 8 amplifications than tumors pertaining to other molecular subgroups [10,28,30].…”
Section: Genomic Profiling Of Blbcmentioning
confidence: 92%
See 3 more Smart Citations
“…This subgroup present a greater genetic complexity compared with other BC subtypes, suggesting a greater degree of genetic instability [28,29]. Bergamaschi [30] found that BLBC show the highest frequency of DNA losses and gains compared with others subtypes and also reported that despite of the highest prevalence of genomic aberrations, BLBC show less genomic 8 amplifications than tumors pertaining to other molecular subgroups [10,28,30].…”
Section: Genomic Profiling Of Blbcmentioning
confidence: 92%
“…But some particular recurrent amplifications described in BLBC are approximately two to three times higher than the other subtypes [10,28] and it includes 7p11.2 involving the region of EGFR, 7q31 affecting caveolin 1, and 12p13 being the amplifications of 8p12 and 17q11.2 associated with poor outcomes [31].…”
Section: Genomic Profiling Of Blbcmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was based on a well-characterised cohort of early stage (I-III) primary operable invasive BC (n=1902) from patients enrolled into the Nottingham Tenovus Primary Breast Carcinoma Series between 1987 and 1998, and managed in accordance to a uniform protocol and has been comprehensively studied with a broad range of markers [9,10]. During the follow-up time within this series, distant recurrence had developed in 578/1902 cases (30 %).…”
Section: Patients and Tumoursmentioning
confidence: 99%